Electrical Abnormalities in Dopaminergic Neurons of the Substantia Nigra in Mice With an Aromatic L-Amino Acid Decarboxylase Deficiency - Ho, Shih-Yin; Chien, Yin-Hsiu; Tsai, Li-Kai; Muramatsu, Shin-ichi; Hwu, Wuh-Liang; Liou, Horng-Huei; Lee, Ni-Chung (Frontiers in Cellular Neuroscience, 2019)
Aromatic L-acid decarboxylase (AADC) deficiency causes severe motor disturbances in affected children. A putamen-targeted gene therapy improves the motor function of patients. The present study investigated the electrical properties of dopaminergic (DA) neurons in the substantia nigra compacta (SNc) of mice with an AADC deficiency (DdcKI). The basal firing of DA neurons, which determines DA release in the putamen, was abnormal in the DdcKI mice, including a low frequency and irregular firing pattern, because of a decrease in the after-hyperpolarization (AHP) amplitude of action potentials. The frequency of spontaneous excitatory postsynaptic currents (sEPSCs) increased and that of spontaneous inhibitory postsynaptic currents (sIPSCs) decreased in the SNc DA neurons from the DdcKI mice, suggesting an elevation in glutamatergic excitatory stimuli and a reduction in GABAergic inhibitory stimuli, respectively. Altered expression patterns of genes encoding receptors and channels were also observed in the DdcKI mice. Administration of a widespread neuron-specific gene therapy to the brains of the DdcKI mice partially corrected these electric abnormalities. The overexcitability of SNc DA neurons in the presence of generalized dopamine deficiency likely underlies the occurrence of motor disturbances.